Reduction of Human T-Cell Leukemia Virus Type 1 (HTLV-1) Proviral Loads in Rats Orally Infected with HTLV-1 by Reimmunization with HTLV-1-Infected Cells - Komori, Kazuya (American Society for Microbiology (ASM), 2006)
Human T-cell leukemia virus type 1 (HTLV-1) persistently infects humans, and the proviral loads that persist in vivo vary widely among individuals. Elevation in the proviral load is associated with serious HTLV-1-mediated diseases, such as adult T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis. However, it remains controversial whether HTLV-1-specific T-cell immunity can control HTLV-1 in vivo. We previously reported that orally HTLV-1-infected rats showed insufficient HTLV-1-specific T-cell immunity that coincided with elevated levels of the HTLV-1 proviral load. In the present study, we found that individual HTLV-1 proviral loads established in low-responding hosts could be reduced by the restoration of HTLV-1-specific T-cell responses. Despite the T-cell unresponsiveness for HTLV-1 in orally infected rats, an allogeneic mixed lymphocyte reaction in the splenocytes and a contact hypersensitivity response in the skin of these rats were comparable with those of naive rats. HTLV-1-specific T-cell response in orally HTLV-1-infected rats could be restored by subcutaneous reimmunization with mitomycin C (MMC)-treated syngeneic HTLV-1-transformed cells. The reimmunized rats exhibited lower proviral loads than untreated orally infected rats. We also confirmed that the proviral loads in orally infected rats decreased after reimmunization in the same hosts. Similar T-cell immune conversion could be reproduced in orally HTLV-1-infected rats by subcutaneous inoculation with MMC-treated primary T cells from syngeneic orally HTLV-1-infected rats. The present results indicate that, although HTLV-1-specific T-cell unresponsiveness is an underlying risk factor for the propagation of HTLV-1-infected cells in vivo, the risk may potentially be reduced by reimmunization, for which autologous HTLV-1-infected cells are a candidate immunogen.